Addition of boceprevir to PEG-interferon/ribavirin in HIV-HCV-Genotype-1-coinfected, treatment-experienced patients: efficacy, safety, and pharmacokinetics data from the ANRS HC27 study. Issue 2 (3rd March 2016) - Poizot-Martin, Isabelle; Bellissant, Eric; Garraffo, Rodolphe; Colson, Philippe; Piroth, Lionel; Solas, Caroline; Renault, Alain; Bourlière, Marc; Halfon, Philippe; Ghosn, Jade; Alric, Laurent; Naqvi, Alissa; et al.
Abstract : Background: Scarce data exist on the efficacy and safety of the PEGylated-interferon/ribavirin/boceprevir regimen in HIV/HCV-coinfected patients who failed to respond to PEGylated-interferon/ribavirin treatment. Objectives: To evaluate the efficacy and safety of this drug regimen and the impact of the addition of boceprevir(BOC) on atazanavir (ATV) or raltegravir (RAL) pharmacokinetic parameters in a subgroup of patients. Methods: In this single-arm phase 2 trial, HIV-1/HCV-genotype-1-coinfected patients received PEGylated-interferonα2b (1.5 μg/kg/week)+ ribavirin (800–1400 mg/day) alone until W4 and with BOC(800 mgTID) until W48. Based on virologic response at W8, the three drugs were stopped or PEGylated-interferon/ribavirin was continued alone until W72. The primary endpoint was SVR at W24 off-therapy (SVR24 ). Results: 64 patients were included. SVR24 was achieved in 53% of patients (CI90% : 43–63%) and in 90% of previous relapsers. In univariate analysis, SVR24 was associated with response to previous HCV treatment, HCV-1b subtype, HCV-RNA decline, ribavirin-Ctrough at W4, and HCV-RNA at W8 but not to fibrosis score, IL28B genotype, or boceprevir-Ctrough at W8. In multivariate analysis, SVR24 remained associated with response to previous HCV treatment [non-responders versus null responders: OR = 5.0(1.3–20.0); relapsers vs. null responders: OR = 28.8(4.9–169.5)]. HCV treatment was discontinued for adverse events in 17% of patients. A 51% decrease in ATV/r-AUC0–8 h ( p < 0.01) and a 57% increase in RAL-AUC0–8 h ( p < 0.01) were observed, although atazanavir/r or raltegravir did not affect BOC-AUC0–8 h significantly. The ATV mean Cthrough fell from 763.8 ng/mL (CI 95%: 230.3–1297.3) without BOC to 507.7 ng/mL (CI 95%: 164–851.4) with BOC. Conclusions: Boceprevir-based regimen demonstrated a high SVR24 rate in treatment-experienced HIV-HCV genotype-1-coinfected relapsers.